PHP 7 programming blueprints : develop production-ready web applications with PHP - Palala, Jose; Helmich, Martin (Community experience distilled., 2016)
Learn how to exploit the impressive power of PHP 7 with this collection of practical project blueprints ? begin building better applications for the web today! About This Book Don't just learn PHP 7 ? follow a diverse range of practical knowledge to get started quickly Take advantage of PHP 7's newest features ? and find out how to use them to solve real development challenges Put PHP to work for performance and scalability ? we'll show you how, you do it! Who This Book Is For The book is for web developers, PHP consultants, and anyone who is working on multiple projects with PHP. Basic knowledge of PHP programming is assumed. What You Will Learn Build versatile projects using the newest features PHP 7 has to offer Learn how to use PHP 7's event-driven asynchronous features Find out how to improve the performance of your code with effective techniques and design patterns Get to grips with backend development and find out how to optimize session handling Learn how to use the PHP 7 Abstract Syntax Tree to improve the quality of your code and make it more maintainable Find out how to build a RESTful web service Build your own asynchronous microservice In Detail When it comes to modern web development, performance is everything. The latest version of PHP has been improvised and updated to make it easier to build for performance, improved engine execution, better memory usage, and a new and extended set of tools. If you're a web developer, what's not to love? This guide will show you how to make full use of PHP 7 with a range of practical projects that will not only teach you the principles, but also show you how to put them into practice. It will push and extend your skills, helping you to become a more confident and fluent PHP developer. You'll find out how to build a social newsletter service, a simple blog with a search capability using Elasticsearch, as well as a chat application. We'll also show you how to create a RESTful web service, a database class to manage a shopping cart on an e-commerce site and how to build an asynchronous microservice architecture. With further guidance on using reactive extensions in PHP, we're sure that you'll find everything you need to take full advantage of PHP 7. So dive in now! Style and approach This product focuses on helping developers build projects from scratch. But more than that, each project will help the reader to learn a new facet or feature of PHP 7 ? it means the reader really will ?learn by doing.'